Raising her voice : African-American women journalists who changed history - Streitmatter, Rodger (University Press of Kentucky, 1994)
Each chapter is a biographical sketch of an influential black woman who has written for American newspapers or television news, including Maria W. Stewart, Mary Ann Shadd Cary, Gertrude Bustill Mossell, Ida B. Wells-Barnett, Josephine St. Pierre Ruffin, Delilah L. Beasley, Marvel Cooke, Charlotta A. Bass, Alice Allison Dunnigan, Ethel L. Payne, and Charlayne Hunter-Gault.